Correlation of Secondary Hyperparathyroidism with Chronic Kidney Disease and its Stages – A Prospective Study. - DR. N. DEEPTHI,; DR. E. DHANDAPANI, (International Journal of Pharma and Bio Sciences, 2018)
Chronic Kidney Disease (CKD) is a clinical syndrome characterized by irreversible renal dysfunction. CKD is a worldwide public health problem. Secondary hyperparathyroidism (SHPT) is an important complication of CKD and is associated with cardiovascular mortality.But it remains under-recognized and under-diagnosed at earlier stages of CKD. The aim of the present study is to analyse the prevalence of SHPT in CKD patients and to demonstrate the correlation of increased parathormone levels with the different stages of CKD in these patientsA cross-sectional study was done over a period of 1 year on 60 CKD patients (31 males, 29 females), aged >20 years. The patients were assessed based on clinical history and a number of laboratory parameters including serum creatinine, calcium, iPTH level and GFR. Patients were seen as inpatients and outpatients in a tertiary care centre With regards to the prevalence of hyperparathyroidism in the 5 stages of CKD, 7 out of 23 patients (30%) in Stage V, 3 out of 13 patients (23%) in stage IV, and 3 out of 12 patients (25%) in Stages III had elevated iPTH values. In our study, 25 out of 36 patients in stage IV and V(69.4%) and 5 out of 24 patients in stages I,II,III (20.8%) had elevated parathormone levels.It was found out that patients with CKD stage IV and V are at 8.6 times higher risk of having increased serum iPTH levels. Thus through simple routine tests of serum iPTH, SHPT can be diagnosed earlier and appropriate treatment can be instituted.